GENETIC RISK FOR BREAST CANCER DEVELOPMENT - Dr. Kausar Abbas Saldera; Dr. Taseer Ahmed Khan; Dr. Syed Mehboob Alam (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: studies in the relation of moderate risk susceptibility genes in the onset of breast ca Methods: Systematic random samples are done on selected Breast cancer patients from tertiary care hospitals in Karachi. The sample size was calculated using an online sample size calculator, Open Epi version 3.01 for case-controls, after inserting a 9.6% proportion of late menopause among cases, at a 5% margin of error and 95% confidence interval. The required sample size for our study was 74 with 37 participants in each group, but we took 100 samples in each group, making it a total of 200. This type of moderate-risk gene research and population-based study in correlation with high-risk gene variation is being conducted first time in the Pakistani population, therefore to see more effective results, we increase the sample size. Subjects were divided into two groups: Cases Group, which included 100 Known Naïve cases of Breast Ca (Females), and Control Group, which included 100 healthy individuals. Results: The results of our study were from 100 breast cancer patients from a homogeneous population (Sindh). We found a correlation between age at diagnosis, family history, and mutation detection rate. Though our study has a limited number of patients, a low frequency of mutation in ATM, CHEK2, and BARD1 genes was reported. Conclusion: Around 20% of hereditary breast cancer is account for variants in the high and moderate breast cancer susceptibility genes BRCA1, BRCA2, TP53, CHEK2, and RAD51C, in Pakistan (Muhammad et al, 2018). Convincingly identified five moderate-risk breast cancer susceptibility genes are: CHEK2, ATM, BRIP1, PALB2, and NBS1 (Rashid et al. 2013). Attempts should be made to develop a real-time assay for the diagnosis of mutations in moderate-risk (ATM, BARD1, and CHEK2) genes.